Peningkatan Kualitas dan Daya Saing UMKM Soappahollic Melalui Kolaborasi Inovasi Produk Sabun Organik - Tries Ellia Sandari; Thesalonika Djumaifin; Gabriella Afe Glorya; Salma Dewi Ambarsari; Salva Dewi Ambarwati; Felix Chandra Pranoto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The potential of the organic soap market is increasingly promising along with the increasing public awareness of the importance of products made from natural and environmentally friendly ingredients. Our organic soap UMKM still faces many challenges, including competition with similar products and lack of access to more modern production knowledge. UMKM Utopia Bodysoap is an UMKM formed by several students of the University of 17 August 1945 Surabaya which aims to provide high-quality natural skin care products to the community. Then collaborate with UMKM Soappahollic with the aim of collaboration between UMKM Soappahollic and Utopia is to increase the competitiveness and profitability of UMKM through the development of innovative and high-quality organic soap products. This collaboration process involves several stages, starting from identifying potential collaboration, knowledge exchange, new product development, product testing and evaluation, to product marketing and sales. The results of the collaboration created a new organic soap recipe that combines the advantages of each, so that UMKM Soappahollic succeeded in improving product quality, product diversification, and business profitability. This community service program has also succeeded in increasing the sustainability of the Soappahollic UMKM business through product diversification and wider market access.